2010
DOI: 10.1093/brain/awq175
|View full text |Cite
|
Sign up to set email alerts
|

The structural plasticity of white matter networks following anterior temporal lobe resection

Abstract: Anterior temporal lobe resection is an effective treatment for refractory temporal lobe epilepsy. The structural consequences of such surgery in the white matter, and how these relate to language function after surgery remain unknown. We carried out a longitudinal study with diffusion tensor imaging in 26 left and 20 right temporal lobe epilepsy patients before and a mean of 4.5 months after anterior temporal lobe resection. The whole-brain analysis technique tract-based spatial statistics was used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
94
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 93 publications
(124 reference statements)
13
94
2
3
Order By: Relevance
“…Data from the current study in a similar cohort suggest that despite apparent normalization of WM DTI metrics at 1 year, alteration in WM microstructure compared to controls is evident about 8 years after PFS, and that this alteration is accompanied by apparent increases in the coherence of the remaining WM structure. Similar findings of FA increase, often accompanied by an increase in AD, have also been reported several months after brain insult in the form of brain surgery, stroke, and traumatic brain injury 30, 31, 32, 33. It is tempting to suggest that this reorganization of the remaining WM structure is the brain's attempt to maintain efficient organization in the face of an event disruptive to the normal trajectory of maturation, and one that has served to maintain neurologic and cognitive function as observed in our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…Data from the current study in a similar cohort suggest that despite apparent normalization of WM DTI metrics at 1 year, alteration in WM microstructure compared to controls is evident about 8 years after PFS, and that this alteration is accompanied by apparent increases in the coherence of the remaining WM structure. Similar findings of FA increase, often accompanied by an increase in AD, have also been reported several months after brain insult in the form of brain surgery, stroke, and traumatic brain injury 30, 31, 32, 33. It is tempting to suggest that this reorganization of the remaining WM structure is the brain's attempt to maintain efficient organization in the face of an event disruptive to the normal trajectory of maturation, and one that has served to maintain neurologic and cognitive function as observed in our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…Functional MRI can be used to define an active network implementing a key function that might be "at risk" with temporal lobe surgery (e.g., verbal fluency), although the validity of this approach needs to be established in prospective studies. 5 Preoperative fMRI has been shown to be sensitive to language and verbal memory laterality 9 and is a known predictor of cog-nitive outcome 24,45 in the setting of epilepsy. For instance, a large fMRI study of verbal and visual memory in patients undergoing left or right anterior temporal lobectomy suggested that presurgical fMRI activation of the ipsilateral anterior temporal lobe was correlated with greater postsurgical memory decline.…”
mentioning
confidence: 99%
“…One published study has reported that a change in fractional anisotropy correlates with good language outcome following temporal lobectomy, but this study lacked a normal control group. 45 In short, rsfMRI can identify the cortical regions communicating within a network; DTI can verify that these regions are anatomically connected; and fMRI can define the cognitive function(s) the network may be communicating about. In practical terms, all three can be gathered during one MRI scanning session with a minimal increase in scanning time and no increase in patient discomfort.…”
mentioning
confidence: 99%
“…In particular, for a subset of 50 patients with glioblastoma or gliosarcoma (WHO Grade IV), there was a significant difference in median survival of 19.3 months (DTI group) versus 11.2 months (control group, p = 0.02), representing a 53.6% reduction in the risk of death over the course of the study. 53 A separate analysis of only WHO Grade IV neoplasms showed a similarly statistically significant survival benefit among patients undergoing DTI-aided resection (19.3 vs 11.2 months). Additionally, the overall rates of GTR in the DTI group (118 cases, 72% GTR) were significantly higher than in the control group that underwent standard neuronavigation (120 cases, 51.7% GTR, p = 0.002).…”
mentioning
confidence: 86%